2024
DOI: 10.1007/s11920-024-01481-9
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Social Media Use on Sleep and Mental Health in Youth: a Scoping Review

Danny J. Yu,
Yun Kwok Wing,
Tim M. H. Li
et al.

Abstract: Purpose of Review Social media use (SMU) and other internet-based technologies are ubiquitous in today’s interconnected society, with young people being among the commonest users. Previous literature tends to support that SMU is associated with poor sleep and mental health issues in youth, despite some conflicting findings. In this scoping review, we summarized relevant studies published within the past 3 years, highlighted the impacts of SMU on sleep and mental health in youth, while also examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 90 publications
0
0
0
Order By: Relevance
“…29 Poor sleep quality led to negative mental health. 29 Similar findings were established by Yu et al 30 The study found that excessive social use, poor sleep quality, and poor outcomes were associated. Some of the reasons why social media use was associated with poor sleep quality was because the sites were interactive platforms which increased mental stimulation and subsequent poor sleep.…”
Section: Reasons Why Social Media Increases the Risk Of Mental Healthsupporting
confidence: 75%
“…29 Poor sleep quality led to negative mental health. 29 Similar findings were established by Yu et al 30 The study found that excessive social use, poor sleep quality, and poor outcomes were associated. Some of the reasons why social media use was associated with poor sleep quality was because the sites were interactive platforms which increased mental stimulation and subsequent poor sleep.…”
Section: Reasons Why Social Media Increases the Risk Of Mental Healthsupporting
confidence: 75%